Quran Education For Special Children: Teacher As Murabbi - Norakyairee Mohd. Raus; Noornajihan Ja‘afar; Nurul Asiah Fasehah Muhamad; Norzulaili Mohd Ghazali; Mahyuddin Hashim; Syed Najihuddin Syed Hassan; Robiatul Adawiyah Mohd @ Amat; Ab. Halim Tamuri; Norshidah Mohamed Salleh; Mohd IsaHamzah (Scientific Research: An Academic Publisher, 2024)
This paper discusses scenarios that occur in the delivery of the National Education Program, focusing the debate on the Special Education teacher professionalism especially teachers of Islamic Studies (IET). The objective of this study is to propose solutions to issues and challenges of the teaching profession by presenting a model of Special Education teacher as Murabbi. The term Murabbi is selected in this model as opposed to Mursyid, Mu’allim, Muaddib, and Mudarris, because Murabbi encompasses the concept of love which is very close to special children as applied in this element. The findings of this study have resulted a model teacher as Murabbi particularly in the context of special education. There are eight characteristics of effective teachers as Murabbi contribute towards upholding the special education system of the country.